Persepsi Guru dan Siswa terhadap Perpustakaan sebagai Sumber Belajar di SD Negeri 5 Bangunrejo Kidul - Nanda Dwi Pratama; Sugiyono; Arif Mustofa (Scholarly Journal of Elementary School, 2026)
Abstract This study aims to describe the inhibiting factors in the utilization of the library and to explore teachers’ and students’ perceptions of the library’s role as a learning resource at SD Negeri Bangunrejo Kidul 5. This research uses a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results of this study indicate that: 1) the inhibiting factors in library utilization include: a) the absence of library staff (librarians); b) limited book collections; and c) the lack of literacy programs and scheduled visits. 2) Teachers perceive the library as an important part of the learning process, but it has not been utilized optimally. 3) Students view the library as a place to gain knowledge, but its use remains limited due to inadequate facilities and lack of comfort. Keywords: teacher perception, student perception, school library, learning resource, library utilization.